(untitled) (Heritage, 2020)
Striving to emphasize the complex and dynamic relationships and mutual connection between the concepts of education and cultures, the aim of this work is to present the role of education in the process of cultural reproduction and the process of cultural production. The work will present, on the one hand, the mechanisms of cultural reproduction in the formal and informal model of education, with particular emphasis on the role of schools in cultural reproduction, while on the other hand they will seek to answer questions about the extent and how education affects cultural production.